2019
DOI: 10.3389/fgene.2019.00752
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Cross Species RNA-seq Meta-Analysis and Machine-Learning Models Identifies the Most Important Salt Stress–Responsive Pathways in Microalga Dunaliella

Abstract: Photosynthetic microalgae are potentially yielding sources of different high-value secondary metabolites. Salinity is a complex stress that influences various metaboliterelated pathways in microalgae. To obtain a clear view of the underlying metabolic pathways and resolve contradictory information concerning the transcriptional regulation of Dunaliella species in salt stress conditions, RNA-seq meta-analysis along with systems levels analysis was conducted. A p-value combination technique with Fisher method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 61 publications
2
31
0
Order By: Relevance
“…Contribution of tetrahydrofolate in cellular one-carbon (C1) pathways and ROS generation at stress condition has been reported previously [51]. Moreover, prior study have proved that SHMT1 switch nitrogen and carbon metabolism to secondary metabolite biosynthesis [11], validating the results of current study. An earlier study also showed that the overexpression of the SHMT1 increases biomass production [52].…”
Section: Kegg Pathway P-value Genessupporting
confidence: 88%
See 3 more Smart Citations
“…Contribution of tetrahydrofolate in cellular one-carbon (C1) pathways and ROS generation at stress condition has been reported previously [51]. Moreover, prior study have proved that SHMT1 switch nitrogen and carbon metabolism to secondary metabolite biosynthesis [11], validating the results of current study. An earlier study also showed that the overexpression of the SHMT1 increases biomass production [52].…”
Section: Kegg Pathway P-value Genessupporting
confidence: 88%
“…In agree with our findings, it has been reported that inactivation of the LACS6 and LACS7 lipid breakdown [58] Another interesting gene that shows a large difference between connectivity in PR versus LG and TR brown module is LCE (Lycopene epsilon cyclase) which is involved in the carotenoids biosynthesis. Transcriptional variation of LCE during the lutein and beta-carotene accumulation circumstances has been reported [11] [4]; however, the changes in the connectivity pattern have not shown up yet, highlighting the efficiency of our integrative approach.…”
Section: Kegg Pathway P-value Genesmentioning
confidence: 94%
See 2 more Smart Citations
“…Exploration of salt stress-responding mechanisms is an inevitable step in resolving these problems. The contribution of ROS and calcium signaling pathway in response to salinity condition has been reported previously 4 . Expressed sequence tag (EST) profiling of D. salina in hypersaline condition also identified 1401 unique responsive transcripts were contributed in protein synthesis, energy, primary metabolism, and protein fate 5 .…”
Section: Introductionmentioning
confidence: 76%